Reduced plasmalogen concentration as a surrogate marker of oxidative stress in elderly septic patients - Brosche, Thorolf; Bertsch, Thomas; Sieber, Cornel; Hoffmann, Ursula (Archives of gerontology and geriatrics, 2013)
Severe sepsis is reportedly accompanied by oxidative stress with a depletion of antioxidant defense. We estimated plasmalogen vinyl ether bond (PVEB) levels in blood plasma of 20 elderly patients with initial severe sepsis, serving as a sensitive surrogate marker of oxidative stress, and compared them with standard markers, i.e., Acute Physiology and Chronic Health Evaluation (APACHE) II score, C-reactive protein (CRP), creatinine, white blood cell and platelet counts. Patients were included in the study and then blood samples were taken within 24 h of the onset of symptoms of severe sepsis. Twenty sex-and age-matched, healthy individuals were included in the study as controls. We measured plasmalogen-derived hexadecanal dimethyl acetal (16: 0 DMA) in isolated phospholipids from EDTA-plasma using gas chromatography. We found a 55% lower concentration of 16: 0 DMA, corresponding to lower levels of PVEB in the patients' plasma compared to the controls (0.26 +/- 0.15 vs 0.58 +/- 0.13 g/100 g; p < 0.001). In all patients' and non-survivors' samples the 16: 0 DMA levels correlated negatively with plasma CRP values (R-S = -0.48 and R-S = -0.70, respectively; p < 0.05), but not with APACHE II scores or other markers. The observed lower baseline content of PVEB may indicate oxidative stress contributing to the sequlae of sepsis, but did not correlate with the outcome or the severity of illness. Serial measurements are needed to validate PVEB as a marker in sepsis. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Lipid oxidation; Sepsis; Elderly patients; Plasmalogens; Oxidative stress